2004
DOI: 10.1080/02652030410001668772
|View full text |Cite
|
Sign up to set email alerts
|

Exposure assessment to synthetic food colours of a selected population in Hyderabad, India

Abstract: An exposure assessment of synthetic food colours was carried out among 1-5- and 6-18-year-old individuals by the food frequency method. Children had an intake of solid food consumption in the range 2-465 g day(-1) and liquid food consumption in the range 25-840 ml day(-1) with added colours. Among the eight permitted colours in India, six were consumed by the subjects of the study. The intakes of some subjects exceeded the acceptable daily intake for colours such as tartrazine, sunset yellow and erythrosine, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 5 publications
5
41
1
5
Order By: Relevance
“…Data in the literature reported that intakes of tartrazine for children in developing countries like United Arab Emirates and India exceeded their ADIs (Husain et al, 2006;Rao et al, 2004;Dixit et al, 2010;Dixit et al, 2011) because children are the major consumers of colored food. The prescribed limit of tartrazine and other synthetic colorants in food product samples was also exceeded (Dxit et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Data in the literature reported that intakes of tartrazine for children in developing countries like United Arab Emirates and India exceeded their ADIs (Husain et al, 2006;Rao et al, 2004;Dixit et al, 2010;Dixit et al, 2011) because children are the major consumers of colored food. The prescribed limit of tartrazine and other synthetic colorants in food product samples was also exceeded (Dxit et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this country, an assessment of the exposure to synthetic food dyes was carried out among 1-5 and 6-18-year-old individuals using the food frequency method. The intakes of some individuals exceeded the acceptable daily intake (ADI) for tartrazine, sunset yellow and erythrosine [21].…”
Section: Resultsmentioning
confidence: 99%
“…Para 12 avaliaram a exposição aos corantes sintéticos em indivíduos de 1 a 5 anos e 6 a 18 anos de idade, de classes sócio-econômicas distintas utilizando QFA. As crianças apresentaram uma ingestão de alimentos sólidos entre 2 e 465g/dia e de 25 a 840mL/dia de alimentos líquidos com adição de corantes.…”
Section: Metodologiaunclassified
“…Tam Di Lorenzo et al 54 Sasaki et al 32 Nettis et al 51 Rao et al 12 García et al Husain et al 13 Freitas et al 15 Inoue et al 30 Tanaka 42 Moutinho et al 2 Elhkim et al 28 Ram & torno do déficit de atenção e hiperatividade. Já em relação à hipersensibilidade não específica, o número de estudos foi maior e os resultados mais consistentes quanto às manifestações clínicas de rinite, urticária e angioedema provocadas pelos aditivos, em particular pelos corantes artificiais.…”
Section: Considerações Finaisunclassified